An interactive system for humanoid robot SHFR-III. (6th April 2020) - Ke, Xianxin; Cao, Bin; Bai, Jiaojiao; Zhang, Wenzhen; Zhu, Yujiao
The natural interaction between human and robot is full of challenges but indispensable. In this article, a human–robot interactive system is designed for humanoid robot SHFR-III. The system consists of three subsystems: multi-sensor positioning subsystem, emotional interaction subsystem, and dialogue subsystem. The multi-sensor positioning subsystem is designed to improve the positioning accuracy, the emotional interaction subsystem uses bimodal emotional recognition model and fuzzy emotional decision-making model to realize the emotion recognition and expression feedback to the interactive objects, and the dialogue subsystem with personal information can complete the response consistent with the default information and avoid conflicting responses .The experimental results show that the multi-sensor positioning subsystem has good environmental adaptability and positioning accuracy, the emotional interaction subsystem can achieve human-like emotional feedback, and the dialogue subsystem can achieve more natural, logical, and consistent responses.